Focally administered succinate improves cerebral metabolism in traumatic brain injury patients with mitochondrial dysfunction. Issue 1 (January 2022) - Khellaf, Abdelhakim; Garcia, Nuria Marco; Tajsic, Tamara; Alam, Aftab; Stovell, Matthew G; Killen, Monica J; Howe, Duncan J; Guilfoyle, Mathew R; Jalloh, Ibrahim; Timofeev, Ivan; Murphy, Michael P; Carpenter, T Adrian; et al.
Following traumatic brain injury (TBI), raised cerebral lactate/pyruvate ratio (LPR) reflects impaired energy metabolism. Raised LPR correlates with poor outcome and mortality following TBI. We prospectively recruited patients with TBI requiring neurocritical care and multimodal monitoring, and utilised a tiered management protocol targeting LPR. We identified patients with persistent raised LPR despite adequate cerebral glucose and oxygen provision, which we clinically classified as cerebral 'mitochondrial dysfunction' (MD). In patients with TBI and MD, we administered disodium 2, 3- 13 C2 succinate (12 mmol/L) by retrodialysis into the monitored region of the brain. We recovered 13 C-labelled metabolites by microdialysis and utilised nuclear magnetic resonance spectroscopy (NMR) for identification and quantification. Of 33 patients with complete monitoring, 73% had MD at some point during monitoring. In 5 patients with multimodality-defined MD, succinate administration resulted in reduced LPR(−12%) and raised brain glucose(+17%). NMR of microdialysates demonstrated that the exogenous 13 C-labelled succinate was metabolised intracellularly via the tricarboxylic acid cycle. By targeting LPR using a tiered clinical algorithm incorporating intracranial pressure, brain tissue oxygenation and microdialysis parameters, we identified MD in TBI patients requiring neurointensive care. In these, focal succinate administration improved energy metabolism, evidenced by reduction in LPR. Succinate merits further investigation for TBI therapy.